Effect of supplementation of micronutrients through different sources on the production performance in crossbred dairy cows - GOWDA, N K S; PRASAD, C S; RAMANA, J V (The Indian Journal of Animal Sciences, 2014)
Study was conducted to know the lactation performance in 12 crossbred cows fed diets with inorganiC and organic source of micronutrient supplementation under each of the dietary treatment. Cows in group 1 were fed concentrate mixture supplemented with 1 % commercial mineral mixture, whereas cows in group 2 were fed with additional green fodder as a strategic supplement in place of 1 % inorganic mineral mixture to meet the mineral needs for 120 days. There was no significant difference in the total dry matter intake in both the groups (10.7S and 10.41 kg). The average daily intake of Ca (55.23 and 41.96 g), Cu (173.19 and 137.10 mg), Zn (800,70 and 625.39 mg) and Mn (1147.49 and 924.11 mg) was significantly (P<0,05) higher in group I fed diet supplemented with mineral mixture than in group 2. However, the average daily intake of P (103.45 and 89.97 g), Mg (32.69 and 27.71 g), Fe (7025 and 6860 mg) and Co (19.73 and 16.53 mg) did not differ significantly amongst the 2 groups indicating that the cows in group 2 fed no minerai mixture could derive these micronutrients through the consumption of additional quantity of green fodder provided to them. The net percentage ofP in the dry matter consumed by the cows in both the groups was higher (0.86-0.96%) than that of Ca (0.42-0.51 %) due to the inclusion of wheat bran and groundnut-cake in the concentrate mixture which are rich sources of P. The unit dietary level ofCu (13-16 ppm), Zn (60-75 ppm), Fe (653-659 ppm), Mn (88-106 ppm) and Co (1.58-1.83 ppm) in the dry matter consumed by the cows in both the groups was higher than the re.commended levels as the concentrate ingredients and green fodder consumed were good sources of these micronutrients. The cows in group 2 fed additional green fodder recorded a non-significant reduction in the average milk yield (4% FCM), 7.69 L/day as compared to 8.08 L per day in group 1 during the 120 days offeeding experiment. Milk composition also did not show significant variation between the groups except the milk ash which was significantly less in group 2. It can be concluded frolp this study that strategic Supplementation of micronutrients through local para grass for crossbred cows producing upto 10 L of milk could meet the trace mineral requirement but the major minerals like Ca and Mg could not be met and required to be supplemented.